Disruption as a Kairos Moment Rethinking the Role of Christian Education in Fostering a Biblically-Grounded yet Compassionate Sexual Ethic - Kia, A Dan; Gilbert Timothy Majesty; Novalyn Olly Tuegeh (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
The disruptive era, characterized by rapid technological advancement, shifting social paradigms, and the globalization of ideas, presents a profound challenge to Christian Education, particularly in the realm of sexual ethics. The pervasive visibility of the LGBT phenomenon often creates a reactive response within Christian communities, leading to a perceived dichotomy between upholding biblical authority and extending Christ-like compassion. This article argues that this disruption should not be viewed merely as a threat but recognized as a Kairos moment a critical and opportune time for theological and pedagogical renewal. Employing a methodology of theological reflection and conceptual analysis, this study explores how Christian educators can move beyond polarized debates to reconceive their role. It proposes a framework for fostering a sexual ethic that is simultaneously biblically grounded and pastorally compassionate. This involves a deliberate rethinking of pedagogical approaches that engage students in critical dialogue with both Scripture and contemporary culture. The article contends that an authentic biblical ethic is not merely about prohibition but about forming disciples who understand God's design for human flourishing, relationships, and sexuality. By seizing this Kairos moment, Christian Education can empower students to navigate a complex world with convictional clarity and empathetic grace, thereby transforming a challenge into a catalyst for a more holistic, effective, and faithful ministry.